2010
DOI: 10.3346/jkms.2010.25.4.634
|View full text |Cite
|
Sign up to set email alerts
|

Primary Squamous Cell Carcinoma in the Testis: A Case Report

Abstract: A 51-yr-old man presented with an enlarged right testis for two months. The radically resected testis showed a relatively well-circumscribed ovoid mass, nearly replacing the normal architecture with central cystic changes. Microscopically, the mass was composed of ovoid shaped tumor cells of a moderately differentiated squamous cell carcinoma (SCC). The central portion of the mass was filled with well-formed laminated keratinous materials and the remnant cavity lined by dysplastic squamous epithelium, indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…3 All case reports have shown similar histological findings with the presence of a cystic cavity containing keratin and the presence of a squamous cell lining. In all the case reports, the epidermoid cysts have transformed into squamous cell carcinomas 4 5…”
Section: Discussionmentioning
confidence: 99%
“…3 All case reports have shown similar histological findings with the presence of a cystic cavity containing keratin and the presence of a squamous cell lining. In all the case reports, the epidermoid cysts have transformed into squamous cell carcinomas 4 5…”
Section: Discussionmentioning
confidence: 99%
“…Most primary testicular tumors are germ cell tumors, and primary testicular SCCs are very rare, with only three cases reported in the English literature [2–5].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, three cases of primary SCCs of the testis have been reported in the English literature [35]. Bryan et al reported a case of a testicular tumor derived from the malignant transformation of an epidermal cyst [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations